Loss modeling of three-leg voltage source inverter fed asymmetrical two-phase induction motor - Kongsuk, Prayad; Kinnares, Vijit (My University, 2016)
This paper presents loss modeling of an asymmetrical two-phase induction motor driven by a three-leg voltage source inverter (VSI) providing unbalanced space vector PWM output voltages. The model parameters are estimated by using a set of measured data obtained from actual motor in conjunction with the genetic algorithms. In order to prove the validity of the loss model, comparison between measured and calculated main and auxiliary winding current waveforms is given by using a superposition method of the equivalent circuit with known fundamental and harmonic voltages of PWM output. Also, experimental loss results are compared with the calculated ones under various conditions. The results show that simulation and experimental results are in good agreement.